1985
DOI: 10.1007/bf02148664
|View full text |Cite
|
Sign up to set email alerts
|

Systemic infection withTrichosporon capitatum in two patients with acute leukaemia

Abstract: Trichosporon capitatum was isolated from the blood of two patients with acute leukaemia who were undergoing induction chemotherapy. Both patients died of their infections, and the fungus was cultured from their tissues after death. Systemic infection was proved by demonstrating the same pattern of fluorescein-labelled lectin staining of fungal elements in the tissues as was shown by the fungal isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…This is the case with B. capitatus, a fungus normally considered a minor component of normal skin flora. Since the first reported B. capitatus infection in 1977 [13], in a patient with aplastic anaemia who underwent bone marrow transplantation, until recently only 5 other cases had occurred in severely immunocompromised patients with haematological malignancies, 4 with acute leukaemia [2,7,11], and 1 multiple myeloma [6]. However, in 1990 Martino et al [8] reported 12 additional cases that had been observed over a period of 6 years in a single institution.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is the case with B. capitatus, a fungus normally considered a minor component of normal skin flora. Since the first reported B. capitatus infection in 1977 [13], in a patient with aplastic anaemia who underwent bone marrow transplantation, until recently only 5 other cases had occurred in severely immunocompromised patients with haematological malignancies, 4 with acute leukaemia [2,7,11], and 1 multiple myeloma [6]. However, in 1990 Martino et al [8] reported 12 additional cases that had been observed over a period of 6 years in a single institution.…”
Section: Discussionmentioning
confidence: 92%
“…Until recent years, 11 cases of B. capitatus infection had been reported [1, 2, 4, 6, 7, 9-11, 13, 14], and only 4 of them were in patients with acute leukaemia [2,7,11]. In 1990, Martino et al [8] reported 12 additional cases observed over a period of 6 years in a single institution.…”
Section: Introductionmentioning
confidence: 96%
“…Blastoschizomyces capitatus sepsis is a rare fungal infection that has been observed in particular in patients with acute leukemia [2,5,6,8]. The main cause is a deep and prolonged neutropenia after intensive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Candida sepsis is frequently encountered while Trichosporon sepsis is only sporadically reported [2,5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Purpuric skin lesions are common, and most VOL. 1,1988 progress to produce large areas of necrosis (46,144) and deep-tissue involvement (5,7,77,82,133). In some instances an oral infection resembling thrush may be seen (92), pneumonia is common (69,106), and hepatitis (71) may occur.…”
Section: Clinical Manifestationsmentioning
confidence: 99%